THE USE OF TERMS AND SENTENCES CONTAINING THE MEANING OF CRITICAL DISCOURSE BY OPINION LEADER IN LEGAL LANGUAGE IN THE CASE OF THE POLICY ON THE USE OF THE COVID-19 VACCINE - Achmad Nashrudin Priatna (Gapenas Publisher, 2022)
This article aims to discuss the discourse conveyed by the opinion leader regarding the policy on the use of the covid 19 vaccine. This article uses a qualitative method with critical discourse analysis and to access and retrieve data in the narrative displayed by online media using N Capture on the N Vivo 12 plus. The conclusion is that critical discourse by opinion leaders shows the existence of an ideology of interest, such as business vaccines or monopoly vaccines originating from one country, so the term